Derivados de Protoporfirina IX funcionalizadas com piperazina e morfolina visando potencializar a atividade fotodinâmica - Franco, Maynne Duarte Suriani (2023)
In the present work, we investigated the photophysical properties, the interaction with the Human Serum Albumin (HSA) protein, incorporation, cytotoxicity and phototoxicity in HeLa-type tumor cells of two novel derivatives of Protoporphyrin IX (PpIX) for application in Photodynamic Therapy (PDT). The modification of the structure occurred in the ramifications of PpIX where portions of piperazine or morpholine were added in order to promote a synergistic effect, increasing its photoactivity and, consequently, its phototoxicity. For this, the derivatives named PpIX-Methyl-Piperazine and PpIX-Morpholine were characterized by spectroscopic techniques and photophysical studies such as the determination of the molar absorptivity coefficient, quantum yield of fluorescence and singlet oxygen, as well as possible reactions of photobleaching using LED performing the comparison with the precursor molecule PpIX, where it was possible to observe that the modifications carried out did not bring great variations in the spectroscopic and photophysical characteristics of the new PpIX derivatives. Aggregation studies in water/methanol and water/DMSO mixtures were also explored, in order to understand the behavior of these molecules in aqueous medium, the majority environment of living cells, where it was possible to perceive that changes in the ramifications of PpIX brought improvement in solubility of PpIX-Methyl-Piperazine and PpIX-Morpholine in aqueous media compared to PpIX. The degree of interaction of HSA with porphyrin compounds was also studied, since it allows the binding of a wide range of endogenous and exogenous compounds and allows the transport of molecules within the human body where an interaction was observed only with PpIX- Methyl-Piperazine. Furthermore, a study of incorporation, cytotoxicity and phototoxicity in HeLa-type tumor cells was performed to evaluate the applicability of these new compounds in PDT, where it was possible to observe a larger phototoxicity of both molecules in comparison with PpIX, making the new molecules excellent candidates for Photodynamic Therapy.